Estudo analítico e interpretativo de 10 canções para canto e piano de Waldemar Henrique compostas entre 1930 e 1937 - Silva, Luciana Pereira da Costa e (2017)
The purpose of this work is to provide subsidies that can help on the interpretative construction process of ten songs of brazilian composer Waldemar Henrique, composed between 1930 and 1937. On the thirty decade scene, the composer from Pará state gained feature as on of the adopters to Vargas Era Nationalist ideology, moving to a canonical center in pursue of visibility and national-wide acceptance, the Rio de Janeiro city. His compose thematic, which aims to evoque the origins nationalism, was in place as multiple voices raise from global shantytown's to compose nationalism strategy. Inside this context, it was assembled historical information that could refer the aesthetics choices of the composer, as well as technical and interpretative aspects utilized by radio singers. Aiming to understand multiple views of study, the approach used was a ontological stamp. . Keywords: Interpretation, Brazilian songs, Waldemar Henrique